PENGARUH MANFAAT DAN KEMUDAHAN PENGGUNAAN TERHADAP SIKAP POSITIF PENGGUNAAN INTERNET BANKING (SURVEY PADA PENGGUNA KLIK BCA SEMARANG) - Willianto, Ayub; Ika, Paskah (Universitas Muhammadiyah Magelang, 2010)
Internet Banking is one of the bank services that enable customers to obtain information, communicate and banking transactions with online system. This research aims to determine the factors that influence the intention to use internet banking by users using Technology Acceptance Model (TAM). The method used for collected data is purposive sampling method which classified as users of Internet Banking BCA in Semarang and the number of samples collected are 100 samples. The analytical technique in this research used multiple regression techniques. This research proved that the factors that influence the intention to use the Internet Banking is perception of usefulness and perceived ease of use. Taken together, the usefulness (U) and ease of use. Taken together, the usefulness (U) and ease of use (EOU) significantly affect on positive attitude of use (ATT). Te value of Adjusted R is 56.2%, it means that the attitude of internet banking users are explained by the variable usefulness (U) and ease of use (EOU) of 56.2%. While the rest of 43.8% explained by other variables.